2009
DOI: 10.2511/rpsd.34.2.33
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Self-Directed Science Concept Learning by Students with Moderate Intellectual Disabilities

Abstract: This investigation focused on the effects of a treatment package including multiple exemplar training, time delay, and a self-directed learning prompt (KWHL chart) on students' ability to complete an inquiry lesson independently and generalize to untrained materials. Three middle school students with moderate intellectual disabilities learned to self-direct themselves through a 15-step task analysis to complete inquiry lessons in chemistry and physical science. All three students achieved mastery across materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 21 publications
(17 reference statements)
0
43
0
Order By: Relevance
“…In the afternoon of Day 2 of training, the final strategy the teachers learned was to conduct an inquiry-based science lesson based on the research of Jimenez et al (2009. In the afternoon of Day 2 of training, the final strategy the teachers learned was to conduct an inquiry-based science lesson based on the research of Jimenez et al (2009.…”
Section: Professional Development Packagementioning
confidence: 99%
See 1 more Smart Citation
“…In the afternoon of Day 2 of training, the final strategy the teachers learned was to conduct an inquiry-based science lesson based on the research of Jimenez et al (2009. In the afternoon of Day 2 of training, the final strategy the teachers learned was to conduct an inquiry-based science lesson based on the research of Jimenez et al (2009.…”
Section: Professional Development Packagementioning
confidence: 99%
“…The professional development in the current study also was gleaned from interventions used in newer research on teaching literacy (Browder, Mims, Spooner, Ahlgrim-Delzell, & Lee, 2008;Browder, Trela, & Jimenez, 2007), mathematics Jimenez, Browder, & Courtade, 2008), and science Jimenez, Browder, & Courtade, 2009). Courtade, Browder, Spooner, and DiBiase (2010) taught middle school special education teachers to implement a 12-step task analysis to instruct students with moderate intellectual disabilities to complete guided-inquiry-based science lessons.…”
mentioning
confidence: 99%
“…The use of a KWHL chart may provide students with a graphic organizer that allows them to be part of cooperative learning groups, demonstrate attention to the lesson, and record information gained. Only one other study currently exists in which students with severe disabilities (Jimenez et al, 2009) have used a KWHL chart in an inclusive science classroom. More research is needed to extend the use of this chart to record student knowledge.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…The use of time-delay procedures in the instruction of students with severe disabilities has been proven effective in the behavioral and academic arena of skills taught to this population (Browder, Ahlgrim-Delzell, Spooner, Mims, & Baker, 2009;Snell & Delano, 2011). Recent science research Jimenez, Browder, & Courtade, 2009) has demonstrated the effectiveness of time delay on student academic outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation